2018
DOI: 10.1007/s40808-018-0432-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of TBM penetration rate from brittleness indexes using multiple regression analysis

Abstract: One of the most important aspects in the excavation of tunnels with a Tunnel Boring Machine (TBM) is the reliable prediction of its penetration rate. This affects the planning and other decision making on the organization of the construction site of the tunneling project, and, therefore, total costs. In this study, raw data obtained from the experimental works of different researchers were used to establish the new statistical models for prediction of rock TBM penetration rate from brittleness indexes, B 1 , B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 43 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Formulas (8)(9)(10)(11)(12)(13) summarize how to calculate the long term state, short term state, and output of a unit in a single instance at each time iteration.…”
Section: Surrounding Rock Class Prediction Model Based On Lstm-svmmentioning
confidence: 99%
See 1 more Smart Citation
“…Formulas (8)(9)(10)(11)(12)(13) summarize how to calculate the long term state, short term state, and output of a unit in a single instance at each time iteration.…”
Section: Surrounding Rock Class Prediction Model Based On Lstm-svmmentioning
confidence: 99%
“…6,7 Jamshidi established regression analysis prediction model of TBM cutting depth and surrounding rock brittleness index by using multiple regression analysis. 8 Yagiz et al respectively adopted intelligent methods such as fuzzy recognition, neural network, and particle swarm optimization to establish the prediction model of TBM excavation rate and rock brittleness index. 9 Qiu et al proposed an advanced classification method of surrounding rock class based on TSP203 system and genetic support vector machine.…”
Section: Introductionmentioning
confidence: 99%
“…So, it was concluded that assessing the performance of rock excavation operations using a rock brittleness index depended on the practical application, e.g., brittleness index, that considered that impact strength parameters may be more suitable for the prediction of percussive drilling penetration rate [29]. Similarly, the effect of rock brittleness on the penetration rate for percussive, rotary and Down The Hole (DTM) drilling operations was investigated using literature data for different types of rocks having varying strength in [30]. Using multiple regression, three equations were proposed, one for each drilling type, to predict the penetration rate using three strength-based brittleness indices [30].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effect of rock brittleness on the penetration rate for percussive, rotary and Down The Hole (DTM) drilling operations was investigated using literature data for different types of rocks having varying strength in [30]. Using multiple regression, three equations were proposed, one for each drilling type, to predict the penetration rate using three strength-based brittleness indices [30].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies noted that predicting the penetration rate is a complex and difficult task because of the interaction between the TBM and rock mass. According to Jamshidi [51], TBM penetration rate directly influences the advance rate, which represents the total distance excavated by the machine divided by the total time. While there is a high cost associated with tunneling projects and using the TBM, utilizing prediction methods, especially ML techniques for predicting the penetration rate of TBM can significantly reduce the total time and cost of the tunneling projects.…”
Section: Introductionmentioning
confidence: 99%